Implementation of Integrated Hybrid PLTS Lathe Machines in UMKM Processing Wood-Based Crafts - Alia*, Nila; Widjanarko, Widjanarko; Perdana, Fengky Adie; Udianto, Pondi; Adiwidodo, Satworo; Puspitasari, Etik; Viyus, Vinan (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Community service activities have a central role in supporting sustainable economic growth, especially in the Micro, Small and Medium Enterprises (UMKM) sector. UMKM processing wood-based crafts, as an integral part of local cultural diversity, face significant energy challenges in sustainable development. In order to overcome this obstacle, this community service activity focuses on implementing a Hybrid Solar Power Plant (PLTS) that is integrated with a lathe for UMKM processing wood-based crafts. The purpose of this community service activity is to provide sustainable solutions for UMKM in terms of reliable energy, while supporting the development of environmentally friendly technologies. The methodology applied includes an initial survey of energy needs, design and installation of the Hybrid PLTS system, lathe operator training, and continuous performance monitoring. This activity involves collaboration with UMKM owners and the local village government to ensure the implementation of solutions that are relevant to real needs and conditions. The results of this activity show that the implementation of Hybrid PLTS integrated with lathes has a significant positive impact on production efficiency and product quality for UMKM. These activities make a real contribution to sustainable economic development at the local level. The results can be used as a model for similar developments in other UMKM sectors. Keywords: Community Service, Hybrid PLTS, UMKM, Processing of Wood-Based Crafts, Sustainable Energy, Renewable Energy